Microscopic evaluation of charged domain wall structure in niobium-based piezoceramics - Urushihara, Daisuke; Kobayashi, Ryota; Martin, Alexander; Asaka, Toru; Webber, Kyle Grant; Kakimoto, Ken Ichi (Applied Physics Letters, 2024)
In this study, we investigated the charged domain wall structure of lead-free piezoceramics (Na0.55K0.45)NbO3 using multiple microscopy techniques. It was found that the oxygen partial pressure during sintering affected the volatilization of A2O (A = Na, K), whereby the resulting vacancies were found to be related to grain sizes. In the polycrystals sintered under the air atmosphere condition, almost all grains show rapid grain growth and complex domain structures containing striped and indefinite shaped domains as revealed by confocal laser microscope and piezoelectric force microscope images. Transmission electron microscopy showed that a part of these domain structures has charged domain walls due to bending the 180° domain walls. The A-site vacancies, such as Na and K, lead to forming large grains and charged domain wall structures.
CRIS-Team Scopus Importer:2025-02-04